2019
DOI: 10.4315/0362-028x.jfp-19-205
|View full text |Cite
|
Sign up to set email alerts
|

Genome Analysis and Multiplex PCR Method for the Molecular Detection of Coresistance to Cephalosporins and Fosfomycin in Salmonella enterica Serovar Heidelberg

Abstract: Heidelberg is among the top three Salmonella enterica serovars associated with human foodborne illness in Canada. Traditional culture and antimicrobial susceptibility testing techniques can be time-consuming to identify Salmonella Heidelberg resistant to cephalosporins and fosfomycin. Rapid and accurate detection of such antibiotic-resistant Salmonella Heidelberg isolates is essential to adopt appropriate control measures. In this study, 15 Salmonella Heidelberg strains isolated from feces of Canadian broiler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 62 publications
0
11
0
Order By: Relevance
“…The presence of the fosA7 gene was identified via WGS, co-existing with bla CTX−M (strain H06) and bla CMY−2 (strain H18). There are other reports that identified fosfA7/bla CMY−2 in SH (Rehman et al, 2019) and fosA3/bla CMY−2 in other enterobacteria (Zhao et al, 2015). This shows that these genes can be co-selected and transported in plasmids IncFIIa and F33: A-: B-for bla CTX−M (Hou et al, 2012;Cunha et al, 2017) and HD0149 for bla CMY−2 blaCMY-2 (Zhao et al, 2015), intensifying the horizontal transfer of genes and MDR profile in SH (Rehman et al, 2017) and other enterobacteria (Zhao et al, 2015).…”
Section: Antimicrobial Resistance Profilementioning
confidence: 71%
See 2 more Smart Citations
“…The presence of the fosA7 gene was identified via WGS, co-existing with bla CTX−M (strain H06) and bla CMY−2 (strain H18). There are other reports that identified fosfA7/bla CMY−2 in SH (Rehman et al, 2019) and fosA3/bla CMY−2 in other enterobacteria (Zhao et al, 2015). This shows that these genes can be co-selected and transported in plasmids IncFIIa and F33: A-: B-for bla CTX−M (Hou et al, 2012;Cunha et al, 2017) and HD0149 for bla CMY−2 blaCMY-2 (Zhao et al, 2015), intensifying the horizontal transfer of genes and MDR profile in SH (Rehman et al, 2017) and other enterobacteria (Zhao et al, 2015).…”
Section: Antimicrobial Resistance Profilementioning
confidence: 71%
“…75% of them belong to serovar SH. In addition, studies show that this gene easily integrates with Salmonella chromosomal DNA (Keefer et al, 2019;Rehman et al, 2019). Fosfomycin is used to treat systemic diseases caused by members of the Enterobacteriaceae family with advanced resistance to antimicrobial drugs, including ESBL producers (Hou et al, 2012).…”
Section: Antimicrobial Resistance Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The detection of resistance genes was performed through a multiplex PCR using specific primers [51] for bla CTX-M , bla TEM and bla SHV and according to Rehman et al [52] for bla CMY . The PCR amplification was carried out using DreamTaq Green PCR master mix (Thermo scientific, Waltham, MA, USA).…”
Section: Analysis Of Resistance Genesmentioning
confidence: 99%
“…Previous research discovered that fosA7 is mainly found on the chromosomes of Salmonella from various sources (human, cattle, sheep, and environment) ( 13 ). Subsequently, this gene was detected in different countries ( 14 16 ). In 2020, a study reported that the FosA identified in Escherichia coli differed from FosA7 protein, which was first reported in Salmonella , and its encoding gene was named fosA7.5 Q86E ( 17 ).…”
Section: Introductionmentioning
confidence: 99%